2002
DOI: 10.1016/s0735-1097(02)01976-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of reversible endothelial dysfunction in hypertensive postmenopausal women

Abstract: This study demonstrates that a significant improvement in endothelial function may be obtained after six months of antihypertensive therapy and clearly identifies patients who possibly have a more favorable prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
365
2
12

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 514 publications
(391 citation statements)
references
References 51 publications
10
365
2
12
Order By: Relevance
“…Endothelial dysfunction has been shown to be a good predictor of cardiovascular events [19][20][21][22][23][24] and has been described as a 'barometer for cardiovascular risk' [25]. We were therefore somewhat surprised by our previous study, which showed that in a normotensive population of patients with type 2 diabetes, spironolactone actually worsened the key prognostic marker of endothelial function [10].…”
Section: Discussionmentioning
confidence: 90%
“…Endothelial dysfunction has been shown to be a good predictor of cardiovascular events [19][20][21][22][23][24] and has been described as a 'barometer for cardiovascular risk' [25]. We were therefore somewhat surprised by our previous study, which showed that in a normotensive population of patients with type 2 diabetes, spironolactone actually worsened the key prognostic marker of endothelial function [10].…”
Section: Discussionmentioning
confidence: 90%
“…Modena and colleagues [72] measured how FMD changed in 400 postmenopausal women before and 6 months after establishment of optimal blood pressure control. Women responding to therapy with >10% FMD improvement had significantly fewer events during 67 month follow-up.…”
Section: Endothelial Dysfunction-a Hallmark Of Cardiovascular Diseasementioning
confidence: 99%
“…These include brachial artery flow-mediated dilatation and venous occlusion plethysmography 1,23 . Severity of hypertension correlates with impairment of endothelial function and anti-hypertensive therapies that improve endothelial function in addition to lowering blood pressure may be associated with greater improvements in overall cardiovascular risk 1,24,25 .…”
Section: Measuring Endothelial Functionmentioning
confidence: 99%
“…The endothelium is an important early target of hypertension and endothelial dysfunction is a risk marker for future cardiovascular events 22 . Targeting Anti-hypertensive strategies that improve endothelial function as well as lowering blood pressure may be more effective in reducing overall cardiovascular risk than approaches which lower blood pressure but have no effect on endothelial function 1,24,104 . Indeed, the Overall, the evidence would suggest that clinicians should consider the vascular effects of anti-hypertensive drugs and non-pharmacological approaches to lowering blood pressure.…”
Section: Why Should We Target the Vascular System In The Treatment Ofmentioning
confidence: 99%